Optical Characteristics of Monochrome and Multilayer Fully Stabilized Zirconia Upon Sintered Cooling Speed - Uasuwan, Pithiwat; Juntavee, Niwut; Juntavee, Apa (European Journal of Dentistry, 2023)
Objectives Firing protocols influence optical properties of dental ceramics. Effects of varying cooling rates of monochrome and multilayer 5 mol% yttria-stabilized tetragonal polycrystalline (5YTZP) on optical properties are subjected for investigation.Materials and Methods Ninety specimens (width, length, thickness = 10 × 20 × 2 mm) were prepared from monochrome (Mo: Cercon xt) and multilayer (Mu: Cercon xt ML with cervical (C) and incisal (I) zoning) 5YTZP. Specimens were sintered and randomly treated with three cooling rates (n = 15/group): slow (S: 5°C/min), normal (N: 35°C/min), and fast (F: 70°C/min). Color appearance (∆EW), color appearance difference (∆Ediff), translucency parameter (TP), contrast ratio (CR), and opalescence parameter (OP) were evaluated in CIEL*a*b* (Commission International de I'Eclairage) system. ∆Ediff was achieved from the coordinate difference of specimen to VITA classic shade A2. Microstructures and compositions were evaluated by scanning electron microscope and energy dispersive spectroscopy. Monoclinic (m), tetragonal (t), and cubic (c) phases were investigated with X-ray diffraction.Statistical Analysis An analysis of variance and Bonferroni multiple comparisons were determined for significant differences (p < 0.05).Results ΔEW of MoF was highest (66.04 ± 1.86), while MuN-I was lowest (62.60 ± 0.86). TP and OP of MoS were highest at 2.85 ± 0.11, and 2.25 ± 0.10, while MuF-I was lowest at 2.16 ± 0.10 and 1.60 ± 0.12. CR of MuF-I was highest (0.948 ± 0.005), while MoS was lowest (0.936 ± 0.005). ΔEdiff of MoF was highest (3.83), while MuN-I was lowest (0.93). Limited grain growth and m-phase composition were indicated upon fast cooling. There were significant differences for all color parameters due to varied materials, cooling rates, and their interactions (p < 0.05) except for interaction in ∆EW and OP.Conclusions Translucency of monochrome and multilayer 5YTZP were different, possibly due to colorant additives. Incisal layer of multilayer 5YTZP was perfectly matched with VITA shade. Increasing cooling speed resulted in smaller grain size, t-m transformation, and finally lower translucency and opalescence. Therefore, to achieve most favorable optical properties, slow cooling rate is recommended.
Keywords: color appearance; contrast; cooling; opalescence; translucency